(untitled) (Agricultural Engineering, 2019)
Currently in Russia and other countries in family farms there is a demand for lowering cost of animal production. Main direction to achieve new terchnological solutions characterized by low energy constumption and high efficiency with maintaining high quality of product (mineral). For example, lately in animal production are acquired concentrates with low unity costs. Realising targets releated with lowering costs of forage production with usage comminution and crease of grain. Previously conducted own researches and literature analises shows, that currently used solutions are characterized by big errors made by construction of the devices, and technology effect of obtained product (grain). The paper presents the criteria for optimalization of technical indicators of shredding devices affecting the quality of the product.